Contribuições dos estudos terminológicos para os profissionais da Saúde Básica do SUS - Tatiana Martins Mendes (2017)
This research, which is based on Science of Lexicon, aims to describe the word variation within regional nomenclature, corresponding to medical, from systematized terminological treatment. It justifies itself by the interest in a larger knowledge about this variation, by the need of disclosure, and because of its contribution in the communication among public health professionals who work in the state of Minas Gerais. The motivation of this research comes from accounts by two groups: a) foreign physician, students from the course of Portuguese Language for the Programa Mais Médicos ["More Doctors Program"] for Brazil; b) Brazilian physicians who teach at the previously mentioned program. Both groups work in the field of health and their accounts suggest that there are two language variations used by people in SUS buildings. One observed variation is in technical language used by professionals of the Family Health team: physicians, nurses, nursing technicians and Community Health Agents; and the other one is observed in general language used by patients, their relatives, servants, among other people. Besides these variations, the groups have also mention the use of more than one word for the same concept and the use of different concepts for the same acronyms and term. In view of these aspects and of the little scope of stigmatized terminological items, our interest is that of studying variation within specialized and popular denominations, respecting the diversity naturally presented by them. The choice of theme has taken into account the communicative situation experienced by professionals attempt to build for a base of data insertion elaborated under the perspective of Terminology and Terminography. The research is based in 14 important technical texts, among specialized articles, dictionary, dissertations and theses, which make up the corpus from which 133 terminological lexical items were extracted. Due to its characteristics, this work fits itself in non-exhaustive modality, and also, from the Communicative Theory of Terminology (CTT), it can be affirmed its descriptive, monolingual, and systematic nature. The process of data collection occurred in semi-automatic form. In order to elaborate the terminographic sheets and to organize the definition database, we used a customized computational tool. The organization of terminological items is in alphabetical order, in format of tab and entry, and its elaboration was done according to epistemological foundations and methodological procedures of CTT. As a result, we present the variation within the two discursive domains that of health professionals and the one used among patients. Lastly, due to its technical and regional character, the produced instruments, the database and the glossary, are intended to health professionals who work in Minas Gerais, within Public Health, a subarea in formation in the field of Health Sciences, for students and researchers of Science of Lexicon, that can also arouse interest in general public.